Untersuchung von Landeigentumsstrukturen in Deutschland: Wem gehört die Landwirtschaftsfläche? - Tietz, Andreas; Bockelmann, Leo (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
The transition towards global sustainability generates substantial land demand, necessitating comprehensive knowledge of land ownership structures to inform decision-making processes. However, in Germany, there is largely a lack of understanding regarding these structures. For the first time, an investigation into ownership data from the cadastral register has been conducted for agricultural land in a widespread random sample of municipalities all over Germany, aiming to bridge this gap. This analysis revealed a high diversity in ownership structures regarding both categorical distribution and regional differences. Land ownership is generally widely dispersed but simultaneously highly unequal. Most land belongs to non-agricultural natural persons. However, the largest individual owners are typically agricultural enterprises and administrative bodies. The concentration rates of ownership do not indicate market-dominant positions held by individual owners. Overall, the results emphasize the necessity of considering local specifics and the high significance of social factors in achieving sustainability goals.